(3NQb GdYhGFO hGSJLdGH GdahGFOs - (3eMeO GdJGhOi Hf eMeO GdSbGWs; (3YHO GdHGSW Hf Ndjd GdMfajs
(3ChdgG (B:s
(3GdMeO ddg Gdhdi GdMejO GdSJGQ , echQ Gddjd Ydi GdfgGQ hHYO , ajbhd GdYHO eMeO GdJGhOi Hf eMeO (B( (3aJMkG (B) (3GdSbGW bOYReJ Ydi LeY JbjjO dWja eNJUQ s
(3BNQgG (B:s
(3hTcQkG dfYeg Gddg , aGdMeO ddg GdPi gOGfG dgPG heG cfG fgJOi dhdG Cf gOGfG Gddg hcGf GdaQGY ef JUfjag HNW eDdag s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs